Prevalence, indications and fetal outcomes of operative vaginal delivery in Sub-Saharan Africa, systematic review, and meta-analysis - Andualem Mebratu; Abbas Ahmed; Addisu Getnet Zemeskel; Asrat Alemu; Tesfaye Temesgen; Wondwosen Molla; Zerihun Figa (BMC, 2023)
Abstract Purpose This systematic review and meta-analysis is intended to assess the prevalence, indications, and fetal outcome of operative vaginal delivery in sub-Saharan Africa. Method In this study, 17 studies with a total population of 190,900 were included in both systematic review and meta-analysis. Search for relevant articles was done by using international online databases (like Google Scholar, PubMed, HINARI, EMBASE, Web of Science, and African journals) and online repositories of Universities in Africa. The JOANNA Briggs Institute standard data extraction format was used to extract and appraise high-quality articles before being included in this study. The Cochran Q and I2 statistical tests were used to test the heterogeneity of the studies. The publication bias was tested by a Funnel plot and Egger's test. The overall pooled prevalence, indications, and fetal outcome of operative vaginal delivery along a 95% CI using forest plots and tables. Result The overall pooled prevalence of operative vaginal delivery in sub-Saharan Africa was 7.98% (95% CI; 5.03-10.65; I2 = 99.9%, P < 0.001). The indications of operative vaginal delivery in sub-Saharan African countries include the prolonged second stage of labor 32.81%, non-reassuring fetal heart rate 37.35%, maternal exhaustion 24.81%, big baby 22.37%, maternal cardiac problems 8.75%, and preeclampsia/eclampsia 2.4%. Regarding the fetal outcome, favourable fetal outcomes were 55% (95% CI: 26.04, 84.44), p =  < 0.56, I2: 99.9%). From those births with unfavourable outcomes, the need for the resuscitation of new-born was highest 28.79% followed by poor 5th minute Apgar score, NICU admission, and fresh stillbirth, 19.92, 18.8, and 3.59% respectively. Conclusion The overall prevalence of operative vaginal delivery (OVD) in sub-Saharan Africa was slightly higher compared to other countries. To reduce the increased applications and adverse fetal outcomes of OVD, capacity building for obstetrics care providers and drafting guidelines are required.